Improving The Health Related Quality of Life of Children with Autism - Amelia Inbam Neelagandan; Mohd Dahlan Hj A Malek (Asian Social Work Journal, 2016)
This is a conceptual paper that investigates how the health related quality of life (HRQOL) of children with autism can be improved. The paper involves a literature review of background information regarding autism, studies documenting the HRQOL of children with autism and factors affecting the HRQOL of children with autism. The aim of this study is to propose an intervention procedure that will help to improve the HRQOL of children with autism. The intervention was developed based on autism clinical practice guidelines and best practice recommendations. Literature shows that HRQOL among children with autism is lower than the general population. Based on the impairment among children with autism, the factors that affect the HRQOL and best practice guidelines for autism intervention, this paper concludes that an ideal intervention program to improve the HRQOL of children with autism would be a parent training program or parent mediated intervention (PMI) that includes strategies to manage challenging behavior, adaptive skills, and social communication skills.